Pengaruh Trust, Ease of Use, dan Price terhadap Repurchase Intention pada Konsumen Tokopedia di Kota Padang - Utama, Danta; Sarianti, Rini (https://jurnal.binamandiri.ac.id/, 2025)
The purpose of this study is to explore in greater depth how consumers’ perceptions of trust, ease of use of the Tokopedia platform, and product prices influence their intention to repurchase on the platform. The main focus of this research is the community of Padang City residents who have previously made purchases on Tokopedia. A total of 150 respondents were involved as samples in this study, selected using a purposive sampling technique. In analyzing the data, the researcher employed a multiple linear regression method. The findings of this study indicate that: 1) the level of trust has a positive and significant effect on consumers’ repurchase intention; 2) the level of ease in using the Tokopedia platform also has a considerable influence on buyers’ interest in making repeat transactions; and 3) price plays an important and significant role in influencing consumers’ desire to shop again.